Urgensi Asuransi Profesi Dalam Perkembangan Bisnis Di Indonesia - Jauhari, Muhammad Fikri (FAIRNESS AND JUSTICE, 2019)
Professional liability insurance (PLI), also called professional indemnity insurance (PII) but more commonly known as errors & omissions (E&O) in the US, is a form of liability insurance that helps protect professional advice- and service-providing individuals and companies from bearing the full cost of defending against a negligence claim made by a client, and damages awarded in such a civil lawsuit. The coverage focuses on alleged failure to perform on the part of, financial loss caused by, and error or omission in the service or product sold by the policyholder. These are potential causes for legal action that would not be covered by a more general liability insurance policy which addresses more direct forms of harm. Professional liability coverage sometimes also provides for the defense costs, including when legal action turns out to be groundless. Coverage does not include criminal prosecution, nor a wide range of potential liabilities under civil law that are not enumerated in the policy, but which may be subject to other forms of insurance. Professional liability insurance is required by law in some areas for certain kinds of professional practice (especially medical and legal), and is also sometimes required under contract by other businesses that are the beneficiaries of the advice or service.